Mass Nouns and Plural Logic - Nicolas, David (Proceedings of the Amsterdam Colloquium, 2007)
There are two main approaches to the semantics of mass nouns (cf. Bunt 1985, Pelletier & Schubert 1989). One uses sets as their semantic values, the other uses mereological sums. Both face difficult problems, notably with sentences like The gold on the table weighs seven ounces (Bunt 1985) and The clay that made up those three bowls is identical with the clay that now makes up these two statues (cf. Cartwright 1965). We propose a new theory able to solve these problems, in a framework different from predicate logic, called plural logic. Our semantics is faithful to the intuition that, if there are eight pieces of silverware on a table, the speaker refers to eight things at once when he says: The silverware that is on the table comes from Italy.